Synthesis of new curcumin analogues from Claisen-Schmidt condensation - Ziani, Nouara; Sid, Assia; Demonceau, Albert; Willem, Quentin; Dassonneville, Benjamin; Lamara, Kaddour (European Journal of Chemistry, 2013)
A series of new curcumin analogues were obtained by Claisen-Schmidt condensation of substituted benzaldehydes with cyclohexanone derivatives using the ratio of 1:2 of ketone to aldehyde in dilute ethanolic solution under base catalyzed (NaOH) conditions at room temperature in good yields. The structures of the synthesized compounds were confirmed by data of IR, 1H NMR, and 13C NMR spectra.